Peningkatan Penguasaan Deep Learning Melalui Project Based Learning untuk Musyawarah Guru Mata Pelajaran (MGMP) PPKn SMA Kabupaten Tabanan - Sujana, I Gede; Mahendra, Putu Ronny Angga; Aryawan, I Wayan; Lestari, Limas Dwi (Civiliza Publishing, 2025)
A community service activity aimed at improving the mastery of Deep Learning concepts through the implementation of the Project-Based Learning (PjBL) learning model for Pancasila and Citizenship Education (PPKn) teachers in Tabanan Regency, Bali. The service methods included workshops, intensive training, mentoring, and the provision of relevant learning resources. Evaluation results showed a significant increase in teachers' understanding of Deep Learning and their ability to design and implement PjBL that integrates technology and local wisdom. This activity is expected to improve the quality of PPKn learning at the high school level, thereby producing competent, creative, and Pancasila-based graduates.